Impact of time of use program on widely distribution generation interconnection in urban power network - Maghami M.R.; Pasupuleti J.; Sundaram S. (Elsevier Ltd, 2025)
The integration of large-scale solar photovoltaic (PV) systems in urban environments requires careful consideration of network planning to ensure a reliable power supply and mitigate challenges. This study focuses on the impact of urban network planning such as wide solar-battery integration and demand response strategy on smart cities. Specifically, it investigates the effects of urban network planning on medium-voltage (MV) networks, with a case study conducted in Malaysia. The substation considered in the research consists of two parallel transformers, 13 lines, and 38 connection points. Each urban load connection point is equipped with 500 kW of solar PV capacity and 1 kWh of battery Energy Storage (BES) to store excess power generated from solar injecting it into the urban network during peak periods. The demand response strategy in this study mainly focuses on the Time of Use (ToU) strategy, encouraging customers to reduce usage during peak load periods and shift it to off-peak periods. Dynamic simulations using Power Factory software are performed to evaluate the effectiveness of the proposed mitigation techniques. The results indicate that each of the demand response and wide solar-battery integration strategies technique significantly improves the performance of the urban network by reducing voltage fluctuations and minimizing power losses. However, the study reveals that integrating these two techniques dramatically improves the system's performance. This study highlights the importance of incorporating urban network planning in smart cities. It enables reliable and efficient utilization of solar energy while maintaining grid stability. ? 2024